A new Symphoromyia in the Middle Eocene Baltic amber (Diptera: Rhagionidae) - Ngo-Muller, Valerie; Nel, Andre (Zootaxa, 2020)
Symphoromyia clerci sp. nov. is described from the Eocene Baltic amber. Even if it has nearly all the characters of the extant species of Symphoromyia subgenus Symphoromyia, it differs from these flies in the short scape, as long as the pedicel (at least twice as long in extant taxa). This fossil is twice as large as those that were previously described from the same amber. These taxa need to be revised to verify their generic attribution. Symphoromyia clerci sp. nov. is the second fossil species attributable to this genus on the basis of ‘modern’ characters. The extant Symphoromyia are frequently hematophagous on mammals, suggesting a similar biology for the Eocene representatives of this genus.